DEVELOPMENT PROJECT MANAGEMENT CAPABILITY OF THE INFRASTRUCTURE PROGRAM. CHERNOBYL CASE - Sergey Bushuyev; Denis Bushuiev; Boris Kozyr (Сучасний стан наукових досліджень та технологій в промисловості, 2019)
The Project Management methodology became one of the bases for the development of the ChNPP. The subject of research is the process of development the project management capability for infrastructure program based on the Chernobyl case. Objective: to develop and apply a tool for development key competence as the organization capability for managing infrastructure program using Chernobyl NPP experience. Tasks: to analyze the historical facts, factors influencing the organizational competence and the possibility of introducing key competence in the organization‘s activities, to obtain a general algorithm for the development project management capability. Research methods: historical analysis, logical generalization, analysis and synthesis, structural analysis. Results: The article considers the key competence of the organization as the main component of the management capability of the complex program the company implements. The facts given above say that the activity which is carried out on a platform of the Chernobyl NPP, in many aspects is innovative and at creation on the Chernobyl NPP of an effective Knowledge Management System of project implementation experience, this knowledge can be applied as the professional development of acting project managers of the ChNPP (for example, to development of target courses), and to transfer of the accumulated experience (through realization of the benchmarking mechanism) to external costumers. The weighed system approach to Knowledge management according to the Methodology of project management can not only render invaluable service to system of preparation of the personnel of the NPP, but also to promote definition of possible ways of collecting, storage and commercial realization of intangible assets of the Conclusions: The state-owned enterprise ChNPP stands at the border of a radical reorganization, when project-oriented business management is implemented alongside the existing standard organizational structure of business management. The activities at the Chernobyl NPP site are in many respects innovative and must be taken into account when organizing work. In order to create an effective project management system, the professional knowledge of the existing Chernobyl NPP project managers must be applied, and the accumulated experience (through the implementation of the benchmarking mechanism) to external customers must be transferred. A weighted systemic approach to knowledge management in accordance with the project management methodology can not only provide an invaluable service to the NPP personnel training system, but also help to identify possible ways of collecting, storing and selling intangible assets.